Where are the Borders of Media Capitalism in Slovenia? - B. Hrvatin, Sandra; Kerševan, Tanja (Javnost-The Public, 1999)
The development in the Slovenian media market suggests that media legislation that is dominated by a free market ideology does not prevent the concentration of media capital. The process of media privatisation takes different courses in print media and in broadcasting. The main problems relate to (1) the non-transparency of privatisation processes, (2) media as family business, (3) cross-media ownership, (4) the impairment of public capital, (5) hostile take-overs. The authors analyse five forms of media ownership concentration in Slovenia: (1) chains -- the same company owns more than the “normal” number of media of the same kind in the state; (2) networks -- a holding company produces programs and distributes them with the help of local stations that are members of its network, but have their own legal independence; (3) cross-media ownership -- media companies include different kinds of media in their portfolio; (4) conglomerates -- corporations whose main activity pertains to a different branch of the economy acquire a media company; (5) vertical integration – mergers in programming production, distribution, publishing activities, etc. Experiences with the “deregulation” demonstrate that just an increase of the number of available channels or the expansion of new print media does not automatically increase the diversity of contents and sources.